Strengthening capacities to implement the multilateral system of access and benefit-sharing:efforts under way and challenges encountered in Bhutan, Burkina Faso, Costa Rica, Cote d''Ivoire, Guatemala, Nepal, Rwanda and Uganda - Halewood, Michael; Vernooy, Ronnie (Food and Agriculture Organization of the United Nations, 2014)
Teams in eight countries (Bhutan, Burkina Faso, Costa Rica, Côte d’Ivoire, Guatemala, Nepal, Rwanda, and Uganda) supported by a grant from the Netherlands to Bioversity International have developed common terms of reference for research and capacity building to support national implementation of the Treaty.58 Activities are carried out in all eight countries under the umbrella of five interrelated themes: 1: National-level multilateral system policy development : common ‘core’ activities (and products); 2: Developing capacity to effectively implement the ITPGRFA: research on policy network structure, actor characteristics and coalitions; 3: Mapping and measuring germplasm interdependence and flows: research on the dynamics of the global crop commons; 4: Linking farmers to the ITPGRFA/MLS: potential and challenges of strengthening access to PGRFA through community-based gene/seed bank; 5: Technology transfer: generating non-monetary benefit sharing in support of conservation and sustainable use of PGRFA. This paper focuses on the steps required to make progress under Theme 1; the steps are described in italics in the next section. The paper also identifies some of the implementation challenges that the eight country teams are facing.